Pengaruh Kualitas Layanan Pramugari Terhadap Kepuasan Penumpang Maskapai Batik Air - Garry Vardy Karwur Karwur; Nadya Ceasarany Ceasarany (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
Competition in air transport services is currently growing rapidly. Batik Air is a Indonesian airline that was founded in March 2013 under the Lion group. The airline offers premium services or so-called full-service flight. The purpose of this research is to determine how much influence the service quality provided by flight attendants has on the level of passenger satisfaction among customers of Batik air. This research applied quantitative approach. The sample of this research is 312 people who have flown with Batik Air on the route Manado - Jakarta route minimum of 2 times. The sampling method used non-probability techniques by using purposive sampling as its foundation. This research used a questionnaire as the research instrument and analyzed using simple regression. The result of the simple regression on this research is Y = -0,535 + 1,101X. The results of this research indicate that there is significant influence between the service quality of flight attendants and the satisfaction of passengers of Batik Air airline. Service quality affects customer satisfaction and has a very high correlation with the figure of 79.6% with the remaining 20,4% affected by the other factor. Further research is recommended on this topic, adding more variables such as passenger loyalty for Batik Air. Keyword: Service Quality, Passenger Satisfaction, Flight Attendants